1999
DOI: 10.1016/s0017-9310(99)00111-8
|View full text |Cite
|
Sign up to set email alerts
|

Microexplosion of aluminum slurry droplets

Abstract: The microexplosion of a slurry droplet is experimentally and theoretically investigated. The microexplosion was considered to be caused by the shell formation and the following pressure build-up in the shell which would be promoted by the suppression of evaporation, subsequent superheating and heterogeneous nucleation of a liquid carrier. Experimentally, the microexplosion phenomena was examined for various surfactant concentrations and particle loading under dierent ambient temperature ranges (500±900 K). To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…(3) Finally, as the viscous shell inhibits vaporization, the flame moves closer to the surface (contraction), heating up the shell quickly beyond the heterogeneous nucleation temperature of xylene and 2-EH acid, initiating disruptions. Moreover, disruptions are only observed if Sn(II)2-EH is present, coinciding with the observations of Wong et al 73,74 and Byun et al 75 In addition, the disruption may also be initiated by soot or nanoparticles, which are formed in the flame and transported back to the droplet by thermophoresis as proposed by Shaw et al 31 Very small particles (d p 200 nm ) from the gas phase can get close to the droplet surface, as was shown by Ben-Dor et al 76 The probability of such an effect may increase as the flame contracts due to a decreasing vaporization rate ( Figure S1 of Supporting Information), thus reducing the force (i.e., drag force due to the Stefan flow) counteracting thermophoresis. Entrapped ambient gas ( Figure 9) may also draw particles into the liquid, where they can act as nuclei.…”
Section: Decomposition During Combustion Of Binary Xylene/ Metal-2-ehsupporting
confidence: 90%
See 1 more Smart Citation
“…(3) Finally, as the viscous shell inhibits vaporization, the flame moves closer to the surface (contraction), heating up the shell quickly beyond the heterogeneous nucleation temperature of xylene and 2-EH acid, initiating disruptions. Moreover, disruptions are only observed if Sn(II)2-EH is present, coinciding with the observations of Wong et al 73,74 and Byun et al 75 In addition, the disruption may also be initiated by soot or nanoparticles, which are formed in the flame and transported back to the droplet by thermophoresis as proposed by Shaw et al 31 Very small particles (d p 200 nm ) from the gas phase can get close to the droplet surface, as was shown by Ben-Dor et al 76 The probability of such an effect may increase as the flame contracts due to a decreasing vaporization rate ( Figure S1 of Supporting Information), thus reducing the force (i.e., drag force due to the Stefan flow) counteracting thermophoresis. Entrapped ambient gas ( Figure 9) may also draw particles into the liquid, where they can act as nuclei.…”
Section: Decomposition During Combustion Of Binary Xylene/ Metal-2-ehsupporting
confidence: 90%
“…Moreover, Wong et al 73,74 showed that only the addition of low-volatile surfactants in slurry droplets suppressed evaporation, superheating, and heterogeneous nucleation of the carrier fuel. Likewise, Byun et al, 75 observed a decrease in the vaporization rate and droplet disruption only when surfactant was present in the slurry droplet. These findings are similar to the aforementioned observations of the Sn(II)2-EH and xylene/2-EH acid solution solutions, for example, (1) Sn(II)2-EH solutions burn initially without perturbation (following the d 2 -law), but the vaporization rate decreases as the concentration of Sn(II)2-EH increases.…”
Section: Decomposition During Combustion Of Binary Xylene/ Metal-2-ehmentioning
confidence: 87%
“…This study demonstrated that disruption of the primary droplet results in secondary atomization, which substantially enhances the overall burning rate of the primary droplet and provides a means for dispersal and ignition of the boron. This behavior was also evidenced by a few other studies involving aluminum and carbon slurries [13,17].…”
Section: Introductionsupporting
confidence: 71%
“…This stage is called ''surfactant flame" because we believe it is due to combustion of the surfactant or its pyrolysis products. None of the previous studies of slurry fuels involving micron-sized particles [6][7][8][9][10][11][12][13][14][15][16][17][18][19] has ever reported an observation of this flame. This stage occurred for all fuel mixtures with surfactant, regardless of the type of base fluid, particle size, or particle concentration.…”
Section: Surfactant Flame Stage (Stage Iv)mentioning
confidence: 90%
See 1 more Smart Citation